SISTEM PAKAR MENDIAGNOSA PENYAKIT OSTEOPOROSIS PADA LANSIA MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Mike Permata Sari; Realize Realize (JURNAL ILMIAH INFORMATIKA, 2019)
Osteoporosis is a disease characterized by reduced bone mass and a change in the microarchitecture of bone tissue resulting in decreased bone strength and increased bone fragility and the risk of fractures. The difficulty of handling cases of osteoporosis due to lack of attention to handle osteoporosis, lack of income, so do not have the cost of consulting a doctor or the public do not have spare time to go to consult a doctor about osteoporosis. Therefore, the study was conducted based on the need for tools for people to diagnose osteoporosis. The tool is a web-based expert system using forward chaining method. Based on the test results, the expert system works quite well with the value of the system accuracy reached 83.3%. This expert system in its consultation can be run by answering each question with yes or no, all responses are tailored to the patient's perceived complaints. The output of this system is the name of disease, symptoms, description and solution.